Retrograde stenting of the superior mesenteric artery is the procedure of choice for dissection of the aorta with mesenteric compromise - Mukherjee, Dipankar (J Vasc Surg Cases Innov Tech, 2019)
Acute mesenteric ischemia secondary to aortic dissection in type A and type B is a true vascular surgical emergency. Presentation can be subtle or dramatic, and time to revascularization is limited before irreversible changes occur. The literature recognizes the catastrophic consequences of acute superior mesenteric artery occlusion and the need for urgent revascularization, often before central aortic repair in type A. There is no optimal revascularization technique described in this scenario. We present a case of type A aortic dissection with acute dynamic and static superior mesenteric artery occlusion and describe treatment that resulted in successful salvage of the bowel and the patient's life.